Aplicación de contabilidad comercial en la empresa Karina Siguenza en la ciudad La Troncal provincia del Cañar, por el período del mes de octubre – diciembre del 2013 - Palomeque Toledo, Boris Luis (2015)
This research paper titled "APPLICATION BUSINESS ACCOUNTING IN THE COMPANY KARINA SIGUENZA IN THE CITY THE CORE CAÑAR PROVINCE, BY MONTH PERIOD OCTOBER - DECEMBER 2013", was developed based on the provisions of the standards general of the National University of Loja, prior to obtain the title of Engineer in Accounting and Auditing CPA requirement. The development of this research work complied with both the general and specific objectives set, thanks to all the facilities provided by the owner of the store, as well as its accounting advisor; all necessary documentation in relation to the financial year for review and further analysis was obtained. With this research we were able to have control of warehouse activities, daily records of the various transactions, inventory control of goods; economic and financial real and reliable information was obtained through the Financial Statements. Having developed this research I came to the conclusion that it is difficult to establish the economic situation of a company without a proper accounting system, to conclude this work at the hardware store one vital tool allowed, why helped develop so correct and accurate each accounting transactions recording them at the time they occur and thus got real, reliable and timely results, they are reflected in the financial statements and these help management to sound decision-making, it is recommended to continue applying for the efficient development of their activities